Congenital Leukemia Report of 2 Cases - S. Untario; Erwin Sarwono; E. K. Kariyadi; Sylviaty M. D.; Netty R. H. T (Indonesian Pediatric Society, 1992)
Two cases of congenital leukemia are reported, one of which was associated with Down's syndrome. Both cases were lymphoblastic as observed morphologically and by the negative Sudanophilia. To the best knowledge of the authors these cases are the first two cases of congenital leukemia reported in the Indonesian medical literature.